Segment-specific generation of Drosophila Capability neuropeptide neurons by multi-faceted Hox cues. - Suska, A.; Miguel-Aliaga, I.; Thor, S. (Developmental Biology, 2011)
In the Drosophila ventral nerve cord, the three pairs of Capability neuropeptide-expressing Va neurons are exclusively found in the second, third and fourth abdominal segments (A2-A4). To address the underlying mechanisms behind such segment-specific cell specification, we followed the developmental specification of these neurons. We find that Va neurons are initially generated in all ventral nerve cord segments and progress along a common differentiation path. However, their terminal differentiation only manifests itself in A2-A4, due to two distinct mechanisms: segment-specific programmed cell death (PCD) in posterior segments, and differentiation to an alternative identity in segments anterior to A2. Genetic analyses reveal that the Hox homeotic genes are involved in the segment-specific appearance of Va neurons. In posterior segments, the Hox gene Abdominal-B exerts a pro-apoptotic role on Va neurons, which involves the function of several RHG genes. Strikingly, this role of Abd-B is completely opposite to its role in the segment-specific apoptosis of other classes of neuropeptide neurons, the dMP2 and MP1 neurons, where Abd-B acts in an anti-apoptotic manner. In segments A2-A4 we find that abdominal A is important for the terminal differentiation of Va cell fate. In the A1 segment, Ultrabithorax acts to specify an alternate Va neuron fate. In contrast, in thoracic segments, Antennapedia suppresses the Va cell fate. Thus, Hox genes act in a multi-faceted manner to control the segment-specific appearance of the Va neuropeptide neurons in the ventral nerve cord.